Web mashups with webmakeup - Díaz, Oscar (2016)
Modding refers to the act of modifying hardware, software, or virtually anything else, to perform a function not originally conceived or intended by the designer. The rationales for modding should be sought in the aspiration of users to contextualize to their own situation the artefact at hand. Websites are not exception. WebMakeup targets mod scenarios where web pages are turned into canvases users can tune to account for their situational, idiosyncratic, and potentially, short-lived needs. By clicking, users turn DOM nodes into widgets. Widgets can next be rearranged, deleted, updated or stored for later reuse in other pages. In addition, widgets can be involved in ?blink? patterns where interactions with a widget might affect the related widgets. This empowers users to tune not only what but also when content is to show up in an AJAX-like way. WebMakeup is publicly available as a Chrome extension.